2017
DOI: 10.1111/iju.13495
|View full text |Cite
|
Sign up to set email alerts
|

Can bladder preservation therapy come to the center stage?

Abstract: Decision-making in urological cancer care requires a multidisciplinary approach for refinement, but its impact on urothelial carcinoma of the bladder has not been fully addressed for the past three decades, except for the latest immunological checkpoint inhibitor approved by the U.S. Food and Drug Administration for metastatic muscle-invasive bladder cancer that is resistant to platinum-based chemotherapy. For the time being, radical cystectomy is the gold standard of curative therapy for muscleinvasive bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…To improve patients' quality of life without compromising their oncological outcomes, trimodal therapy (TMT) consisting of transurethral resection of the bladder tumor, chemotherapy and radiation therapy has emerged as a potential alternative treatment option that preserves the bladder. 1 The incidence of renal deterioration was comparatively high after RC. Urinary tract obstruction induced by ureteroenteric stricture was the leading cause of rapid renal function decline after surgery, whereas hypertension, diabetes mellitus and acute pyelonephritis were associated with the development of late renal function deterioration.…”
Section: Supporting Informationmentioning
confidence: 98%
“…To improve patients' quality of life without compromising their oncological outcomes, trimodal therapy (TMT) consisting of transurethral resection of the bladder tumor, chemotherapy and radiation therapy has emerged as a potential alternative treatment option that preserves the bladder. 1 The incidence of renal deterioration was comparatively high after RC. Urinary tract obstruction induced by ureteroenteric stricture was the leading cause of rapid renal function decline after surgery, whereas hypertension, diabetes mellitus and acute pyelonephritis were associated with the development of late renal function deterioration.…”
Section: Supporting Informationmentioning
confidence: 98%
“…Relationship of frailty with treatment modality selection in patients with muscle-invasive bladder cancer (FRART-BC study) demonstrated comparable survival outcomes when patients were appropriately selected (7)(8)(9)(10)(11)(12)(13). However, no level 1 evidence supported the definitive selection criteria for TMT.…”
Section: Original Articlementioning
confidence: 99%
“…Radical cystectomy is considered the treatment of choice for muscle-invasive bladder carcinoma[ 1 - 6 ]. Surgery may not be possible, however, for patients with locally advanced tumors or for those considered medically unfit[ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%